Defining Smart City Governance - Calzada, I (TM Forum, 2016)
Dr Calzada has given a keynote conference as expert insight on 'Defining Smart City Governance' into the programme of the three-day conference in the premier Smart City capital of China, Yinchuan, organised by TM Forum Smart City InFocus 2016.